‘Iddah dalam Q.S. Ath-Thalaq [65]: 1 - Ambrullah, Ahmad Rasid (Syams, 2023)
Prohibition from leaving the house during the 'iddah period is an obligation thatmust be carried out by an ex-wife after divorce as stated in Q.S. Ath-Thalaq [65]: 1.Regarding the prohibition on leaving the house in Q.S. Ath-Thalaq [65]: 1 for women whoare undergoing the 'iddah period in turn becomes a problem if it is connected to contemporaryphenomena so that the discussion of 'iddah with its various rules in the Qur'ān is importantto review, especially regarding the understanding and meaning of Q.S. Ath-Thalaq [65]: 1regarding the prohibition on leaving the house for women during the 'iddah period from theperspective of the interpretation of Indonesian mufassir. This research is qualitative researchand uses library research. The data collection technique uses document study which refers tothe main document, namely the Al-Qur'ān and the tafsir books used include Tafsir An-Nur, Al-Azhar and Al-Miṣhbāḥ. Furthermore, the data analysis technique usesdescriptive-comparative methods and uses a socio-historical approach to sharpen the researchresults. The result of this research is the interpretation of Q.S. Ath-Thalaq [65]: 1perspective of Indonesian mufassir in Tafsir An-Nur, Al-Azhar and Al-Miṣhbāḥ havedifferent views where Hasbi in Tafsir An-Nur is the only person who interprets Q.S. Ath-Thalaq [65]: 1 regarding the strict prohibition of leaving the house for women who areobserving the 'iddah period, namely not allowing women to leave their house at all so thatHasbi's interpretation can be classified as a textual meaning, while Hamka in Tafsir Al-Azhar, interprets semi-textually, where Hamka is of the view that the prohibition onleaving the house for women during the 'iddah period is absolute, but the customs of a societyare taken into consideration in implementing the 'iddah rules. Furthermore, MuhammadQuraish Shihab in Tafsir Al-Miṣhbāḥ in understanding a verse of the Qur'an prioritizesthe context before going to the text, so that Quraish Shihab's interpretation of Q.S. Ath-Thalaq [65]: 1 really considers the situation and conditions of modern society, especiallytoday, so Quraish Shihab's interpretation of Q.S. Ath-Thalaq [65]: 1 is contextual.